The development of aerobic and anaerobic fitness with reference to youth athletes - Armstrong, N.; Welsman, J. (Journal of Science in Sport and Exercise, 2020)
Purpose: To challenge current conventions in paediatric sport science and use data from recent longitudinal studies to elucidate the development of aerobic and anaerobic fitness, with reference to youth athletes. Methods: (1) To critically review the traditional practice of ratio scaling physiological variables with body mass and, (2) to use multiplicative allometric models of longitudinal data, founded on 1053 (550 from boys) determinations of 10-17-year-olds` peak oxygen uptake (VO2) and 763 (405 from boys) determinations of 11-17-year-olds` peak power output (PP) and mean power output (MP), to investigate the development of aerobic and anaerobic fitness in youth. Results: The statistical assumptions underpinning ratio scaling of physiological variables in youth are seldom met. Multiplicative allometric modelling of longitudinal data has demonstrated that fat free mass (FFM) acting as a surrogate for active muscle mass, is the most powerful morphological influence on PP, MP, and peak VO2. With FFM appropriately controlled for, age effects remain significant but additional, independent effects of maturity status on anaerobic and aerobic fitness are negated. Conclusions: Ratio scaling of physiological variables with body mass is fallacious, confounds interpretation of the development of anaerobic and aerobic fitness, and misleads fitness comparisons within and across youth sports. Rigorous evaluation of the development of anaerobic and aerobic fitness in youth requires longitudinal analyses of sex-specific, concurrent changes in age- and maturation-driven morphological covariates. Age and maturation-driven changes in FFM are essential considerations when evaluating the physiological development of youth athletes.